UN 2030 Agenda for Sustainable Development: Contradictions in social protection for young people and older people - Mutange, Zurema Domingos; Mateus, José Dias; Pimentel, Rosalinda Chedian; Soares, Nanci (Seven Editora, 2024)
This article aims to analyze the interlocution between social protection for young people and the elderly and the "UN 2030 Agenda for Sustainable Development", using historical-dialectical materialism as a theoretical-methodological mediation for the interpretation of the same interlocution, based on bibliographic and documentary research on the subject. Through the research, results were obtained according to which salaried work is the founding criterion of social protection in contemporary society; the UN (and all its agendas) has constituted the political dimension of capital since its origin, which imposes on allied states a certain form of social protection, thus responding to the expressions of the social question; Both young people and the social group that categorizes the elderly are converted into mere commodities that appear in the form of a labor force whose strength is maintained by social protection. DOI:https://doi.org/10.56238/sevened2024.026-047